Sàng khôn as A Theorizing Tool in Mobility Education - Ngoc Ba Doan (Education Sciences, 2017)
The current virtual and physical mobility of humans, ideas, knowledge and epistemologies has major implications for education, especially in settings where English is seen as the default medium of instruction. While diversity is inherent in mobility, English-only pedagogy is a denial of the richness and potential of diverse resources learners bring with them through their mobility. This paper reports a philosophical stance and pedagogical practices employed by a lecturer in English language education at an Australian university. It argues that students’ full linguistic resources and epistemologies, known as sàng khôn, contribute to their agency and can be used as tools to theorise new knowledge in the context of their mobility education.